(3QSGdI aj EjeGf CHj WGdHs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3GdfLa s)
(3ChdgG (B:s
(3aEfj oeKHJ HJhajb Gddg YR hLd heG jgH aj GdJSOjO WQakG ef GdebGd hGdeYfi Ydi EjeGf CHj WGdH Hf YHOGdeWdH Hf gGTe Hf YHO efGa QVj Gddg Yfg hCQVGg s
(3BNQgG (B:s
(3OdGFd EjeGfg hJUOjbg HQShd Gddg Udi Gddg Ydjg hSde caGjI hHdhZ hGdMeO ddg QH GdYGdejf hUdhGJg hSdGeg Ydi eMeO hBdg GdWGgQjf s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(1/433) s
Keywords: (3GdJhMjO hGdedd hGdfMds